Anti-Inflammatory Activity Test of Ethanolic Extract of Transdermal Patch Crinum asiaticum L Against Male Wistar Rats Induced by Carrageenan - Robiatun Rambe; Armansyah Maulana Harahap; Yurike Elanda; Ali Affan Silalahi; Yetty Machrina (Sumatera Medical Journal, 2025)
Background:Crinum asiaticum leaves are recognized for their wound healing properties, particularly in treating abrasive or inflamed wounds. Objective: This study aims to evaluate the efficacy of a transdermal patch prepared from Crinum asiaticum leaf extracts in reducing inflammation. Methods: The preparation involved applying coconut oil to the fruit, roasting it, and then using it on the affected area. Leaf samples and extracts were utilized to formulate transdermal patches at three different concentrations (1%, 3%, and 5%). The patches were assessed organoleptically for thickness, weight uniformity, folding resistance, and pH. Results: The findings demonstrated that the 5% concentration transdermal patches exhibited superior anti-inflammatory effects compared to the 1% and 3% concentrations. This suggests that higher concentrations of Crinum asiaticum extracts enhance the therapeutic potential of transdermal applications. Conclusion: The study concludes that transdermal patches formulated with Crinum asiaticum leaves are effective in reducing inflammation, with 5% concentration offering the highest efficacy. Further research is recommended to explore the clinical applications of these patches in wound management.